The popular within the context of the modern city of Bogota: The Wizards Kings and Epiphany Festivities at the Egipto district - Giraldo Lozano, Lina Patricia [UNESP] (Univ Barcelona, Servei Publicacions, 2015)
The Wizards Kings and Epiphany festivities at the Egipto district is one of the oldest religious parties in Bogota, and stands out dues to its blend of religiousness, playfulness, and the profane: a specific moment of catholic zeal along with the most diverse elements of popular culture such as games, dance, food, drinks, etc., which are all part of the pagan universe. The modernization characteristics of the city themselves, from the later half of the 20th century, imply an accelerated urbanization process, and thus imbue into the event a range of new content, as well as new specificities. There is a transformation in the different senses of the party, which go through the institutionalization of the State and private companies; something which bestows new elements which enrich the festivity, as it becomes more massive, though it also impoverishes it due to the fact that it determines its functions according to State and market logics.
Keywords: Bogota; Popular Culture; Modernization